Die allmähliche Preisgabe des Nationalstaates: Von „Kongresspolen“ zum „Weichselgouvernement“ — gibt es Parallelen im Hinblick auf EU-Rechtssetzungen und deren Vollzug? Betrachtungen zu staatlicher Souveränität und Identität im Verhältnis zu nebenstaatlichem und supranationalem Recht am Beispiel Polen - Schröder, Wolfgang (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
In the light of Poland’s historical experience of more than 100 years under foreign sovereignty, especially that of the Russian from 1815 to 1918, Poland’s current reservations about the danger of an excessive transfer of national sovereign rights to European Union institutions. In the view of the undersigned, partial aspects of this transfer aff ect certain principles of European primary law.
Keywords: sovereignty; national state; culture; European Union; foreign rule